2023
DOI: 10.1186/s12889-023-15694-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between food insecurity and lifestyle behaviors among university students: a comparative study between Lebanon and Germany

Abstract: Background Food insecurity is a common public health problem in both developed and developing countries. This study aimed to profile food insecurity among university students in a developed country with stable economic circumstances (Germany) and a developing Mediterranean country undergoing a severe economic and financial crisis (Lebanon) and examine the associations between food insecurity and lifestyle behaviors (i.e., physical activity, sleep, and adherence to a healthy eating pattern, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…The HFIAS tool has been found to have satisfactory reproducibility and validity in studies among university students. Validation studies among university students reported good internal consistencies, with Cronbach a values ranging from 0.920 in Germany, 0.750 in Lebanon, and 0.916 among South African university students (26,28,29). The current study yielded a good internal consistency of 0.950.…”
Section: Food Insecuritysupporting
confidence: 52%
“…The HFIAS tool has been found to have satisfactory reproducibility and validity in studies among university students. Validation studies among university students reported good internal consistencies, with Cronbach a values ranging from 0.920 in Germany, 0.750 in Lebanon, and 0.916 among South African university students (26,28,29). The current study yielded a good internal consistency of 0.950.…”
Section: Food Insecuritysupporting
confidence: 52%
“…We further categorised the data as food secure, mildly food insecure, moderately food insecure or severely food insecure following the guidelines published by Coates et al (2007). This scale has been used in several countries with a wide range of populations including university/college students (Abu et al, 2023;Abu & Oldewage-Theron, 2019;Celik et al, 2023;Rizk et al, 2023;Theodoridis et al, 2018;Wagner et al, 2021), as this tool can distinguish household food security status across different cultural contexts. Furthermore, in the current study, the HFIAS showed strong internal consistency, with a Cronbach's alpha value of 0.805 in the sample.…”
Section: Household Food Insecuritymentioning
confidence: 99%
“…Eurostat's findings confirm this diversity of eating styles, especially when differences between genders and different levels of education and income are taken into account (EUROSTAT, 2022b). Today's eating styles are influenced by a variety of factors, including food insecurity (Rizk et al, 2023), food scandals (Rieger et al, 2016), sustainability issues in food production (Allen and Prosperi, 2016;Liu and McCarthy, 2023), environmental pollution (Pink et al, 2022), and ethical concerns (Fanzo, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Eurostat’s findings confirm this diversity of eating styles, especially when differences between genders and different levels of education and income are taken into account (EUROSTAT, 2022b). Today’s eating styles are influenced by a variety of factors, including food insecurity (Rizk et al. , 2023), food scandals (Rieger et al.…”
Section: Introductionmentioning
confidence: 99%